Manusia: Keharusan dan Kemungkinan Pendidikan - Lukman Ali; Muhammadong (Jurnal Ilmiah Pendidikan Holistik (JIPH), 2022)
Human nature from the creator's point of view is a very perfect creature because it is equipped with a different mind from other creatures. Humans are equipped with reason and thoughts that can make humans continue to think and develop their minds. Education is essentially an effort to civilize humans or to glorify humans. For the implementation of education properly and appropriately, we need a science that examines in depth how education should be implemented. In this case there is what is called the necessity of education, which contains humans as creatures who need to be educated and need to educate themselves. And the possibility of education which contains about humans as beings who can be educated. The analysis technique in this paper is thematic analysis. The results of the study show that with the necessity and possibility of education, the target (human) will become a learner and also an educator in accordance with the nature and principles that exist, so that humans can become useful people for themselves and others